Hairpin loop to hairpin loop: a full-length assembly of the ASFV genome using Oxford Nanopore long-read sequencing - Phadphon, Poompat; Sonthirod, Chutima; Thaweerattanasinp, Theeradej; Shearman, Jeremy R.; U-thoomporn, Sonicha; Saenboonrueng, Janya; Wanitchang, Asawin; Tangphatsornruang, Sithichoke; Jongkaewwattana, Anan; Pootakham, Wirulda (Frontiers in Microbiology, 2025)
Short-read assembly of the African swine fever virus (ASFV) genome is challenging due to the presence of inverted terminal repeat (ITR) and hairpin loop sequences, which often cause ambiguity in contig reconstruction. In this study, we employed Oxford Nanopore long-read sequencing to assemble a full-length ASFV genome from passage 50 of an ASFV strain adapted to MA-104 cells. We identified duplicated reverse complementary reads from the ITR and hairpin loop regions, which, if not properly analyzed, could lead to an inaccurate assembly that falsely represents these complex regions. Our findings highlight the power of long-read sequencing for resolving complex viral genomes and reveal potential challenges for other viruses with similar terminal structures.